The effect of profitability ratio on market capitalization in insurance companies listed in Kuala Lumpur stock exchange / Siti Nurliyana Borhani - Borhani, Siti Nurliyana (Faculty of Business Management, 2017)
Market capitalization is true measure of a company‟s value. This study aims to examine the effect of profitability ratio on market capitalization. Thus, the objective of the study is to know one of the profitability ratios, which can influence the market capitalization of Malaysian insurance companies. To study market capitalization is taken as a dependent variable and profitability ratios (Return on Assets, Return on Equity and Return on Investment) are selected as independent variables. Sample of 9 insurance companies have been taken for the study. The period of the study is five years from 2011 to 2015. The finding shows that there is significant relationship between Return on Equity (ROE) and Return on Investment (ROI) toward market capitalization for the companies operating in the insurance sector in Malaysia. It indicates that there is an effect of ROE and ROI on Market Capitalization. In respect of the effect of Return on Assets (ROA) upon Market Capitalization, the result indicated that there is no effect of ROA on market Capitalization for the companies operating in the insurance sector in Malaysia. Keywords: Profitability Ratios, Market Capitalization, Malaysian Insurance Companies